Re-Orienting the Sex Discrimination Argument for Gay Rights after Lawrence v. Texas - Williams, Jeffrey A. (Columbia Journal of Gender and Law, 2019)
This claim of sex discrimination in the petitioners’ brief in Lawrence v. Texas,2= a case about criminalized homosexual sodomy, must seem quite out of place to some. Respondents simply belittled its importance in their reply. They chose not to address the extensive argument that the National Organization for Women (NOW) briefed defending sex discrimination. They also did not consider the dissent in the Texas Court below, which similarly relied on a sex discrimination argument. In fact, the sex discrimination argument in Lawrence was far more than a footnote. But the respondents devoted their attention to sexual orientation claims instead. The Supreme Court did, too. Sex discrimination claims for homosexuals have surfaced again in the arena of same-sex marriage challenges. In Massachusetts, the Supreme Judicial Court rejected the treatment of homosexuals as second-class citizens but recognized at least a terminological difficulty! In San Francisco, Mayor Newsom has very clearly relied on a sex equality claim. Only recently, the New York courts have also entered the same-sex marriage debate, with an opinion by Judge Doris Ling-Cohan that affirmed marital rights for same-sex couples without relying on the sex discrimination argument. The legal relationship between sex discrimination and sexual orientation discrimination arguments is currently unclear because the courts have been reluctant to protect homosexuals under any legal theory. As that reluctance passes, however, the need to examine this relationship has become pressing.